2017
DOI: 10.1007/s11427-017-9263-6
|View full text |Cite
|
Sign up to set email alerts
|

The persistent prevalence and evolution of cross-family recombinant coronavirus GCCDC1 among a bat population: a two-year follow-up

Abstract: Bats are connected with the increasing numbers of emerging and re-emerging viruses that may break the species barrier and spread into the human population. Coronaviruses are one of the most common viruses discovered in bats, which were considered as the natural source of recent human-susceptible coronaviruses, i.e. SARS-COV and MERS-CoV. Our previous study reported the discovery of a bat-derived putative cross-family recombinant coronavirus with a reovirus gene p10, named as Ro-BatCoV GCCDC1. In this report, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…Different to the genetically diverged HKU9-CoV, this virus is highly conserved (Figure 2). BtEoCoV-GCCDC1 has only been found in south Yunnan Province so far [54,55]. In addition, there are other bat CoVs that have been identified in China: Rhinolophus ferrumequinum α-CoV HuB-2013 [8], Myotis ricketti α-CoV Sax-2011 [8,37], Nyctalus velutinus α-CoV SC-2013 [8], Scotophilus bat CoV 512 [37], Hipposideros bat β-CoV Zhejiang2013, and a Murina leucogaster bat CoV, which has been described as the evolutionary ancestor of PEDV [37].…”
Section: Other Bat Covs In Chinamentioning
confidence: 99%
“…Different to the genetically diverged HKU9-CoV, this virus is highly conserved (Figure 2). BtEoCoV-GCCDC1 has only been found in south Yunnan Province so far [54,55]. In addition, there are other bat CoVs that have been identified in China: Rhinolophus ferrumequinum α-CoV HuB-2013 [8], Myotis ricketti α-CoV Sax-2011 [8,37], Nyctalus velutinus α-CoV SC-2013 [8], Scotophilus bat CoV 512 [37], Hipposideros bat β-CoV Zhejiang2013, and a Murina leucogaster bat CoV, which has been described as the evolutionary ancestor of PEDV [37].…”
Section: Other Bat Covs In Chinamentioning
confidence: 99%
“…In etiologic studies with convincing evidence, a series of such fatal diseases in humans have been confirmed or hypothesized to be caused by bat-borne viruses such as Hendra virus (HeV), Ebola virus (EBOV), Marburg virus, and coronaviruses, including severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV) [410]. Similarly, fetal diseases in livestock have also been associated with emerging viruses of bat origin, such as the fatal disease outbreak of pigs in China, which was found to be caused by a novel coronavirus, swine acute diarrhea syndrome coronavirus (SADS-CoV), from bats [11,12]. Furthermore, it was shown that influenza-like viruses, termed H17N10 and H18N11 circulating among bats in Central America, may act as an ancient influenza reservoir [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…While exact ecological conditions where genetic exchanges between different pathogens and their evolution took place is often difficult to trace, but as described earlier, the possibility of these changes can increase proportionally with the time spend together inside a tolerant host. For example, longitudinal observation of one population of R. leschenaultii bats for two years found recombinants of RdRp (RNA dependent RNA polymerase) and p10 genes in Ro-BatCoV GCCDC1 within as early as five months since the initial surveillance began (Obameso et al, 2017).…”
Section: Role Of Tolerance In Spillover and New Infectionsmentioning
confidence: 99%